Profil Pelajar Pancasila Dalam Persfektif Pendidikan Agama Islam - Musdalipah Musdalipah; Rustang Bin Lapude; Ahmad Muktamar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Pancasila student profile is designed to answer one big question, namely students with what kind of profile (competency) the Indonesian education system wants to produce. In this context, the Pancasila Student Profile has a competency formulation that complements the focus on achieving Graduate Competency Standards at each level of educational unit in terms of cultivating character in accordance with Pancasila values. The Pancasila student profile competency pays attention to internal factors related to the identity, ideology and ideals of the Indonesian nation, as well as external factors related to the life context and challenges of the Indonesian nation in the 21st century which is facing the industrial revolution 4.0. Apart from that, Indonesian students are also expected to have the competence to become democratic citizens and become superior and productive human beings in the 21st century. Indonesian students are expected to be able to participate in sustainable global development and be resilient in facing various challenges. The Pancasila student profile has various competencies which are formulated into six key dimensions. The six are interrelated and strengthen each other so that efforts to realize a complete Pancasila student profile require the development of all these dimensions simultaneously. by students, but rather increase appreciation and practice in everyday life. Islamic religious education is a benchmark for how Islam and its people have played their role in various social, political and cultural aspects. Therefore, by following developments in the modern era, Islamic religious education throughout Indonesia must increasingly develop and be distributed in all areas of life in today's world. The position of Pancasila Education and Islamic Religious Education is very important, namely that it is related to Islamic sciences which are the foundation in life that need to be known and understood properly.